Banco pela internet ou banco por aplicativo m??vel: a for??a do engajamento e da experi??ncia com a marca - Garzaro, Daniela Menezes (2019)
This dissertation aims to verify the effect of interactivity and social presence on the engagement of clientsof Banks, and how these relationships affect the brand experience, and its effect on brand satisfaction, and brand loyalty, evidencing the differences in the digital banking service channels (internet and mobile application). In order to answer the following research question: what is the influence of the digital banking service channels (internet and mobile application) on the relationship between engagement and brand experience? The research is quantitative and descriptive. A survey was conducted by means of online questionnaires, answered by 413 users of digital banking service channels (internet and mobile application). The data were analyzed by Structural Equations Model (SEM), using the non-parametric PLS-MGA group method, Smart PLS 3.0 release. The relationships between the constructs were confirmed, as well as the mediated effect proposed to social presence and engagement. There were found differences between the two groups on the relationship between social presence and engagement. The work is finalized with the final considerations, limitations of the study and suggestion for future studies.